Problems of Neonatal Jaundice in Indonesia - H.E. Monintja; B. Wirastari; N. Kadri; A. Aminullah; S. Muslichan (Indonesian Pediatric Society, 1979)
This study revealed the incidence of neonatal jaundice in the Dr. Cipto Mangunkusumo Hospital Jakarta to be 32.1%, i.e 42.97% in low birth weight infants and 29.70% in fulllerm infants. No pathological basis was proven in many cases. The factors which may cause pathological jaundice according to the frequency are as follows: infections, anoxia and hypoxia, hemolysis due to G6PD deficiency, multiple factors and hypoglycemia etc. This study also revealed that 69.5% of jaundiced infants had bilirubin concentration of more than 10 mg%. Analysis of the factors showed that most of them were preventable.